An Environmental Scan of Virtual "Walk-In" Clinics in Canada: Comparative Study - Matthewman, Spencer; Spencer, Sarah; Lavergne, M Ruth; McCracken, Rita K; Hedden, Lindsay (JMIR Publications, 2021)
BackgroundCanada has been slow to implement virtual care relative to other countries. However, in recent years, the availability of on-demand, "walk-in" virtual clinics has increased, with the COVID-19 pandemic contributing to the increased demand and provision of virtual care nationwide. Although virtual care facilitates access to physicians while maintaining physical distancing, there are concerns regarding the continuity and quality of care as well as equitable access. There is a paucity of research documenting the availability of virtual care in Canada, thus hampering the efforts to evaluate the impacts of its relatively rapid emergence on the broader health care system and on individual health. ObjectiveWe conducted a national environmental scan to determine the availability and scope of virtual walk-in clinics, cataloging the services they offer and whether they are operating through public or private payment. MethodsWe developed a power term and implemented a structured Google search to identify relevant clinics. From each clinic meeting our inclusion criteria, we abstracted data on the payment model, region of operation, services offered, and continuity of care. We compared clinics operating under different payment models using Fisher exact tests. ResultsWe identified 18 virtual walk-in clinics. Of the 18 clinics, 10 (56%) provided some services under provincial public insurance, although 44% (8/18) operated on a fully private payment model while an additional 39% (7/18) charged patients out of pocket for some services. The most common supplemental services offered included dermatology (15/18, 83%), mental health services (14/18, 78%), and sexual health (11/18, 61%). Continuity, information sharing, or communication with the consumers' existing primary care providers were mentioned by 22% (4/18) of the clinics. ConclusionsVirtual walk-in clinics have proliferated; however, concerns about equitable access, continuity of care, and diversion of physician workforce within these models highlight the importance of supporting virtual care options within the context of longitudinal primary care. More research is needed to support quality virtual care and understand its effects on patient and provider experiences and the overall health system utilization and costs.